1996
DOI: 10.2307/2061781
|View full text |Cite
|
Sign up to set email alerts
|

Compromised birth outcomes and infant mortality among racial and ethnic groups

Abstract: Research based on hospital records demonstrates that many births classified as normal according to conventional demographic measurement are intrauterine growth-retarded (IUGR) when evaluated clinically; also, in addition to birth weight and gestational age, it is necessary to focus on a third dimension, maturity, in analyses of birth outcomes. Although clinical studies allow more precise classification, the small number of cases tends to result in unreliable estimates of rates and in loss of generalizability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 30 publications
0
46
0
1
Order By: Relevance
“…Demographers have employed a less extensive classification for some analyses in which low birth weight (LBW) infants are divided into premature births (<37 weeks gestation and < 2500 grams) and those who are intrauterine growth retarded (37 or more weeks gestation and < 2500 grams), with all births weighing 2500 grams or more classified as normal (Kallan 1993;Hummer et al 1995). More recent modifications proposed by Frisbie et al (1996Frisbie et al ( , 1997 distinguish heavy premature infants (<37 weeks, ≥2500 grams) and also incorporate the fetal growth ratio (Kramer et al 1988(Kramer et al , 1989 as a means of identifying immature births that would not be detected using conventional measures.…”
Section: Birth Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographers have employed a less extensive classification for some analyses in which low birth weight (LBW) infants are divided into premature births (<37 weeks gestation and < 2500 grams) and those who are intrauterine growth retarded (37 or more weeks gestation and < 2500 grams), with all births weighing 2500 grams or more classified as normal (Kallan 1993;Hummer et al 1995). More recent modifications proposed by Frisbie et al (1996Frisbie et al ( , 1997 distinguish heavy premature infants (<37 weeks, ≥2500 grams) and also incorporate the fetal growth ratio (Kramer et al 1988(Kramer et al , 1989 as a means of identifying immature births that would not be detected using conventional measures.…”
Section: Birth Outcome Measuresmentioning
confidence: 99%
“…Several relatively recent demographic studies (Frisbie, Forbes and Pullum 1996;Frisbie et al 1997;Hummer et al 1999) have considered alternative specifications that make finer-grained distinctions than do the conventional dichotomous classifications of birth weight and gestational age. These alternative categorizations of birth outcomes follow in a long tradition (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Further, employment while pregnant may enhance health at birth by increasing family income via pregnancy earnings. Increased family income may enhance health at birth by facilitating the purchase of health inputs such as medical supplies and prenatal physician care, and, for example, at least some evidence indicates that prenatal care enhances birth outcomes (Grossman and Joyce, 1990;Frank et al, 1992;Joyce, 1994;Warner, 1995;Frisbie, Forbes, and Pullum, 1996;and Liu, 1998). 5 Further, increased family income may lift (or keep) the family out of poverty.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Certainly poverty has been associated with less healthy children. For example, poverty is associated with an increase in the probability of infant mortality, low birth weight, and poor health at birth (Currie and Cole, 1993;Guo and Harris, 2000;and Stockwell, Swanson, and 4 Many have found that health at birth is enhanced by prenatal care (Grossman and Joyce, 1990;Frank et al, 1992;Joyce, 1994;Warner, 1995;Frisbie, Forbes, and Pullum, 1996;and Liu, 1998). Currie and Grogger (2002) note that prenatal care can reduce the incidence of premature birth by detecting and treating vaginal infections with antibiotics.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…[16][17][18] These racial and socioeconomic disparities in health persist, even in the face of overall declines in all-cause and infant mortality, because mortality among more privileged groups has declined at the same rate as, or in some cases, faster than, the health of those with fewer economic and social privileges. 19,20 One way to reduce disparities is to identify and implement effective strategies to improve health within communities with fewer resources. Public health professionals and community residents alike continue to seek such strategies.…”
mentioning
confidence: 99%